Serum Levels of IL-10 and IL-22 Cytokines in Patients with Psoriasis - Mohammad Reza Sobhan; Mahmood Farshchian; Ali Hoseinzadeh; Hamid Reza Ghasemibasir; Ghasem Solgi (Iranian Journal of Immunology, 2016)
Background: As a chronic inflammatory condition, psoriasis results from an interaction between genetic and immunologic factors in a predisposing environment. In spite of compelling evidence for the role of T cells and cytokines in psoriasis, interleukin (IL)- 10 and IL-22 have not been sufficiently investigated. Objective: To assess the serum levels of IL-10 and IL-22 in patients with psoriasis compared to healthy controls. Methods: A total of 28 patients with psoriasis were compared with 28 age and sexmatched healthy subjects. Psoriasis Area and Severity Index (PASI) criteria were used to measure the severity of the disease. Serum levels of IL-10 and IL-22 were measured in both groups and compared. Results: The mean serum level of IL-10 was 89.5±18.7 in patients compared to 117.2±23.4 pg/ml in the controls (p=0.36). Also, serum level of IL-22 was 284.1±49.7 in patients versus 425.4±82.8 pg/ml in control group (p=0.17). There was a significant direct correlation between levels of IL-10 and IL-22 in patients group (p=0.0005). The clinical severity of psoriasis was significantly correlated with high levels of IL-22 (p<0.0001).Conclusions: The decreased levels of IL-10 in psoriatic patients and direct correlation between higher levels of IL-22 and disease severity support the clinical implication of both cytokines in psoriasis.